Lost in Shangri-la [large type] : a true story of survival, adventure, and the most incredible rescue mission of World War II - Zuckoff, Mitchell (HarperLuxe, 2011)
Describes the 1945 odyssey of three plane crash survivors in New Guinea who endured a harrowing journey through the jungle to seek help, their encounter with a primitive tribe who had never seen white people, and their eventual rescue by a band of paratroopers.